The Relationship between Nagari Government Policy and Customary Law - Sahur, Muhammad; Krisnawansyah, Yahya; Putri, Rianda Prima (STIA Adabiah, 2023)
This research aims to determine and analyze the relationship between Nagari government policies and Guguak Hilir Sungai Limau customary law. The method used in the research, entitled The Relationship between Nagari Government Policy and Customary Law in Nagari Guguak Kuranji Hilir, Sungai Limau District, Padang Pariaman Regency, is a descriptive qualitative research method. Researchers select informants according to certain predetermined criteria. These criteria must be appropriate to the researcher's topic. Those selected must also be considered credible to answer the research problem. However, in future research, researchers may also use the snowball technique adapted to the conditions or situations in the field. In this research, the data collection techniques used were observation, interviews, and documentation. In analyzing research data obtained from research results in the field, researchers used the Miles & Huberman model of data analysis. Based on the research results, it was found that the Nagari government policy and customary law in Nagari Guguak Hilir Sungai Limau are an interesting phenomenon and reflect the legal pluralism that exists in Minangkabau. In the policy aspect of the Nagari Guguak Hilir Sungai Limau Government, the traditional principles of salika Nagari and pusako sajaka tepi are a strong basis. The Nagari government in Nagari Guguak Hilir Sungai Limau has succeeded in achieving a balance between legal pluralism and maintaining the values and norms of customary law that exist in Nagari itself.